Aplikasi Paklobutrazol dan KNO3 untuk Meningkatkan Kualitas dan Kuantitas Bunga Potong Anggrek Dendrobium ‘Sarifah Fatimah’ - Murni Dwiati (Fakultas Biologi | Universitas Jenderal Soedirman, 2007)
A study on the effect of interactions between paclobutrazole and KNO3 application on the quality and quantity of Dendrobium ‘Sarifah Fatimah’ orchid cutflower was conducted. The experiment was arranged in a Randomized Complete Block Design (RCBD) employing two factors, i.e. paclobutrazole doses (100, 150, 200 ppm) and KNO3 doses (100, 200, and 300 ppm), replicated three times respectively providing 27 experimental units. The results showed that paclobutrazole and KNO3 application had significant effect on the reproductive parameters. To accelarate flowering and higher quality and quantity of the flowers, paclobutrazole of 100 ppm were applied at 2 and 5 weeks after adaptation combined with KNO3 of 100 ppm applied twice at interval of 3 weeks after paclobutrazole application could be given.